Heterogeneous photocatalysis for selected atypical antipsychotic removal from river waters - Regulska, Elżbieta; Karpińska, Joanna (Видавництво Львівської політехніки, 2011)
Heterogeneous photocatalysis of selected atypical antipsychotic, namely olanzapine, was examined. Photocatalytic degradation of above mentioned pharmaceutic was investigated in deionized and river water solution in the presence of titanium dioxide as a photocatalyst. River water samples were collected from Narew and Marycha, which run in the east of Poland. Studied irradiation sources included ultraviolet radiation and simulated solar light. Photodegradation efficiency and the presence of possible arising intermediates were examined by highperformance liquid chromatography with ultraviolet detection. Photocatalytic degradation efficiencies were significantly enhanced in the river water solutions compared to the synthetic deionized water. They also reached higher levels in case of utilizing solar light instead of ultraviolet radiation. Degradation extent was assessed by the HPLC peak area for olanzapine after exact time of irradiation.
Keywords: atypical antipsychotic; heterogeneous photocatalysis; olanzapine; titanium dioxide